1986
DOI: 10.1104/pp.81.2.444
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Fructan Metabolism in Leaves of Barley (Hordeum vulgare L. cv Gerbel)

Abstract: Excised primary leaf blades of barley (Hordeum vulgare L. cv Gerbel) rapidly synthesized large quantities of fructan in the light and, upon transfer to the dark, they rapidly degraded it again. In the course of such a light/dark cycle the activities of sucrose-sucrose-fructosyltransferase (SST), fructan hydrolase, and invertase were measured in cell-free extracts of the blades. SST activity increased 20-fold within 24 hours in the light and disappeared again upon transfer to the dark during a similar period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
1
3

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 14 publications
(30 reference statements)
9
106
1
3
Order By: Relevance
“…The synthesis carried out in vitro showed that the reaction is quite linear but faster during the first 100 hours slowing down after this (Figure 7). This pattern is regular and showed that reaction occurs without apparent inhibition, mainly caused by sucrose which is known to inhibit many enzymatic reactions when its concentration is high [16].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The synthesis carried out in vitro showed that the reaction is quite linear but faster during the first 100 hours slowing down after this (Figure 7). This pattern is regular and showed that reaction occurs without apparent inhibition, mainly caused by sucrose which is known to inhibit many enzymatic reactions when its concentration is high [16].…”
Section: Resultsmentioning
confidence: 96%
“…Although it was established that net fructan accumulation only occurs when the rate of synthesis exceeds the rate of degradation in the vacuole [16], an imbalance occurs during the postharvest life which lead to the exhausting of the FOS reserve in onion tissues. Beside these biosynthetic activities, up to this date, no work reported the biosynthesis of new FOS in onion bulbs during storage, or in any other liliaceous plants as well.…”
Section: Introductionmentioning
confidence: 99%
“…A stimulating effect of pyridoxaI-HCI on fructosyltransferases was also observed by other authors (Koops and Jonker, 1996;Simmen etal., 1993;Wagner and Wiemken, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of phosphorylated substrate causes a retarded glycolysis in spite of Numerous studies provide direct or indirect evidence linking fructan metabolism to environmental stress (Archbold, 1938;Hendry, 1987;Pollock & Cairns, 1991). The relationship between fructans and the response of plants to low temperature has often been described (Wagner, Wiemken & Matile, 1986;Tognetti et al, 1990). However, whether fructans are directly involved in the mechanism of cold adaptation is still debatable because their accumulation may be the result of an increased content of sucrose for very difTerent reasons (Wagner, Keller & Wiemken, 1983;Cairns & Pollock, 1988).…”
Section: Discussionmentioning
confidence: 99%